2018
DOI: 10.4103/jnrp.jnrp_337_17
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of Parkinson's Disease: Experience of Niger

Abstract: Background:Parkinson's disease (PD) is a chronic neurodegenerative pathology with unknown etiology. It is characterized clinically by the classic triad that associated tremors, bradykinesia, and rigidity. In Niger, there are no data on PD.Aims:We aimed to provide the demographic and clinical profile of PD in patients from Niger to create a database on PD in Niger.Patients and Methods:We conducted a retrospective study at the Neurology Outpatient Clinic of the Hôpital National de Niamey (HNN, Niger) over a peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
2
6
0
1
Order By: Relevance
“…As with other literature, there were more men with PD in this study too [10-11]. In a Japanese study, female gender was more commonly associated with PD [12].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…As with other literature, there were more men with PD in this study too [10-11]. In a Japanese study, female gender was more commonly associated with PD [12].…”
Section: Discussionsupporting
confidence: 80%
“…Similar results have been seen in other studies too. In some studies, non-motor symptoms have been more commonly reported [10,15]. In this study, 63% patients with PD showed signs of cognitive impairment.…”
Section: Discussionsupporting
confidence: 49%
“…The amyloid beta accumulation promotes oxidative stress and leads to mitochondrial dysfunction. As for PD, it is a chronic neurodegenerative disease without a clear etiology and is characterized by the classic triad of tremors, bradykinesia, and rigidity (32). Research has shown that >50% of patients with PD will develop dementia within 10 years after the initial diagnosis (33).…”
Section: Discussionmentioning
confidence: 99%
“…Une étude en zone rurale de Tanzanie a trouvé une prévalence de 40/100000 habitants [7]. Une étude, faite au Niger sur les données hospitalières de 2009 à 2013 a montré une fréquence hospitalière de 1,47 % [8]…”
Section: Introductionunclassified